Quantifying Optimal Growth Policy - Volker Grossmann; Thomas M. Steger; Timo Trimborn (Verein für Socialpolitik, 2010)
This paper develops a comprehensive endogenous growth framework to derive the optimal growth policy. The analysis is novel in that we capture important elements of the tax-transfer system and fully take into account transitional dynamics in our numerical analysis. US firms can currently about fully deduct their R&D and capital costs for calculating taxable corporate income. Our analysis suggests that the status quo policy leads to severe underinvestment in both R&D and physical capital. We find that firms should be allowed to deduct between 2- 2.5 times their R&D costs and about 1.5-1.7 times their capital costs from sales revenue. Implementing the optimal policy mix is likely to entail huge welfare gains.
Keywords: O30; H20; O40; 330; Economic growth; Endogenous technical change; Optimal growth policy; Tax-transfer system; Transitional dynamics